Medical marijuana in neurology - Benbadis, Selim R; Sanchez-Ramos, Juan; Bozorg, Ali; Giarratano, Melissa; Kalidas, Kavita; Katzin, Lara; Robertson, Derrick; Vu, Tuan; Smith, Amanda; Zesiewicz, Theresa (Expert review of neurotherapeutics, 2014)
Constituents of the Cannabis plant, cannabinoids, may be of therapeutic value in neurologic diseases. The most abundant cannabinoids are Δ(9)-tetrahydrocannabinol, which possesses psychoactive properties, and cannabidiol, which has no intrinsic psychoactive effects, but exhibits neuroprotective properties in preclinical studies. A small number of high-quality clinical trials support the safety and efficacy of cannabinoids for treatment of spasticity of multiple sclerosis, pain refractory to opioids, glaucoma, nausea and vomiting. Lower level clinical evidence indicates that cannabinoids may be useful for dystonia, tics, tremors, epilepsy, migraine and weight loss. Data are also limited in regards to adverse events and safety. Common nonspecific adverse events are similar to those of other CNS 'depressants' and include weakness, mood changes and dizziness. Cannabinoids can have cardiovascular adverse events and, when smoked chronically, may affect pulmonary function. Fatalities are rare even with recreational use. There is a concern about psychological dependence, but physical dependence is less well documented. Cannabis preparations may presently offer an option for compassionate use in severe neurologic diseases, but at this point, only when standard-of-care therapy is ineffective. As more high-quality clinical data are gathered, the therapeutic application of cannabinoids will likely expand.